Effectiveness and Safety of Sofosbuvir/Ledipasvir and Paritaprevir/ritonavir/Ombitasvir + Dasabuvir in Patients with Chronic Kidney Diseases: Results from ERCHIVES. (4th October 2017) - Butt, Adeel; Ren, Yanjie; Puenpatom, Amy; Arduino, Jean Marie; Kumar, Ritesh; Abou-Samra, Abdul-Badi
Abstract: Background: Chronic kidney disease (CKD) was a relative contraindication to HCV treatment in the interferon/ribavirin era due to poor tolerability and lower efficacy. Our aim was to determine the effectiveness treatment completion, and safety of sofosbuvir/ledipasvir (SOF/LDV) and paritaprevir/ritonavir/ombitasvir/dasabuvir (PrOD) regimens in persons with CKD. Methods: We identified all persons started on a SOF/LDV or PrOD regimen in ERCHIVES before 30 April 2016. We excluded those with missing HCV genotype, or eGFR values. We determined treatment completion, sustained virologic response (SVR) rates and proportion of persons with worseningrenal function or developing grade 3/4 anemia. Results: We identified 9, 837 persons on SOF/LDV, 3, 826 on SOF/LDV+RBV, 1, 017 on PrOD and 2, 944 on PrOD+RBV. Genotype 1a was the predominant genotype for SOF/LDV+RBV (77.3% no RBV; 70.0% with RBV) and PrOD+RBV (79.5%) groups, while only 4.3% of PrOD with no RBV group were genotype 1a. Among treated patients, the prevalence of patients with stage 4–5 CKD was 0.8% (SOF/LDV + RBV), 1.1% (SOF/LDVno RBV), 2.2% (PrOD +RBV) and 5.4% (PrOD no RBV). Among 13, 663 total persons on SOF/LDV, 67.8% completed treatment while the treatment completion rate of those on PrOD was 74.0% (N = 2, 932/3, 961) (Table 1). The overall SVR rates of persons on SOF/LDV or PrOD regimens were 96.3%. A drop in treatment completion rates was seen in CKD stage 4–5 and those on PrOD+RBV, but the impact of RBV on SVR was unclear. While about one-third of the persons with a CKD stage 1–2 experienced a >10 mL/minute/1, 73m 2, about 15% decline among those with CKD stage 3. The incidence of grade3/4 anemia by CKD stages increased significantly across the treatment groups. Grade 3/4 anemia ranged from 9.7% (SOF/LDV) to 21.8% (PrOD) among patients with CKD stage 4–5 (Table 2). Conclusion: SVR rates among persons treated with SOF/LDV or PrOD were high in the CKD population despite 22% not completing the treatment regimen. Incidence of grade3/4 anemia increased significantly in CKD stage 4–5 across the treatment groups. Disclosures: A. Butt, Merck: Investigator, Grant recipient.A. Puenpatom, Merck: Employee, Salary. J. M. Arduino, Merck: Employee, Salary. R. Kumar, Merck: Employee, Salary